Learning Chef for Linux and macOS : using Chef and InSpec in a decentralized environment to fully automate the configuration of a fleet of computers - Taylor, Mischa (O'Reilly Media, 2017)
"Chef is a popular configuration management tool used to quickly automate an entire fleet of machines. Chef allows you to define repeatable administration patterns in code tailored to your organization's specific needs. While typically deployed in conjunction with a Chef Server, Chef expert Mischa Taylor shows the numerous applications for Chef that do not require a Chef Server. You will start using Chef to do useful infrastructure automation immediately for your organization. In this course, he shows you how to use Chef to fully automate the configuration of a fleet of Linux and/or macOS development machines and how to validate the configuration "test first" with InSpec. Designed for learners with basic command line interface skills who are new to Chef, the infrastructure automation skills acquired in this course will be completely applicable when you're ready to take on Chef Server."--Resource description page.